PENENTUAN MASA KADALUARSA LIKOPEN DARI BUAH TOMAT (Lycopersicum pyriforme) TERCAMPUR MALTODEKSTRIN DALAM KEMASAN KAPSUL - Kostriana Daniel; Mappiratu Mappiratu; Ni Ketut Sumarni (KOVALEN: Jurnal Riset Kimia, 2017)
The investigation about the determination of the expired time of lycopene made from tomato (Lycopersicum pyriform) which was mixed with maltodextrin in capsule packaged has been done. The aim of the research is to determine the ratio of lycopene extract to maltodextrin for yielding lycopene with the highest purity degree and to determine the expired time. The applied ratio of lycopene to maltodextrin were 5:10, 7.5:10, 10:10, 10:7.5, 10:5 (w/w). Those samples were stored at room temperature for 10 weeks. Spektrofotometri UV-VIS was used to analyze the samples. The results showed that the highest purity degree was reached at the ratio of 10:10 (39.56%). The best expired time at the ratio of 5:10 was reached at 12.93 weeks.Keywords: Tomato, lycopene, lycopene mixed maltodextrin, purity degree, expired